2019
DOI: 10.1002/smll.201804473
|View full text |Cite
|
Sign up to set email alerts
|

Advance in Close‐Edged Graphene Nanoribbon: Property Investigation and Structure Fabrication

Abstract: The absence of dangling bonds in close‐edged graphene nanoribbons (CEGNRs) confers upon them a series of fascinating properties, especially when compared with cylindrical carbon nanotubes and open‐edged GNRs. Here, the configuration of CEGNRs is described, followed by the structure‐related properties, including mechanical, thermal, electrical, optical, and magnetic properties. Based on the unique structures and extraordinary properties, their potential applications in a variety of fields, such as field‐effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 120 publications
(193 reference statements)
2
16
0
Order By: Relevance
“…When d 0 >3nm, the vdW-LC approach (red line) shows a sharp decrease of P c , corresponding to a tube diameter where interactions between the PTM and the tube walls dominate, while the curvature energy is negligible for such diameters. SWCNT simulations (red circles), show a self-collapse diameter of 5.3 nm, in good agreement with the experimental data reported; about 5.1 nm is cited in the review of He et al [15]. This agreement allows then to fit γ F −C (see Table 1), in the vdW-LC model for SWCNT.…”
Section: Numerical Simulations Experiments and Model Validationsupporting
confidence: 85%
See 2 more Smart Citations
“…When d 0 >3nm, the vdW-LC approach (red line) shows a sharp decrease of P c , corresponding to a tube diameter where interactions between the PTM and the tube walls dominate, while the curvature energy is negligible for such diameters. SWCNT simulations (red circles), show a self-collapse diameter of 5.3 nm, in good agreement with the experimental data reported; about 5.1 nm is cited in the review of He et al [15]. This agreement allows then to fit γ F −C (see Table 1), in the vdW-LC model for SWCNT.…”
Section: Numerical Simulations Experiments and Model Validationsupporting
confidence: 85%
“…As expected, these points are mainly found in the collapsed domain. We have underlined a particular point from the work of He et al [15] (yellow square), which corresponds to the determination of the critical collapse diameter by observations of many SWCNT. This point should then lie on the limiting curve, and is found to be in very good agreement with the prediction of our model.…”
Section: Numerical Simulations Experiments and Model Validationmentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, curvature on graphitic structures has been sometimes proposed as a hypothesis to explain an observed D band on graphene wrinkles, loops, and graphitic polyhedral crystals, while the contribution of topological defects could not be ruled out nor quantified. Flattened carbon nanotubes (FCNTs, scheme in Figure d) can be considered as few-layer graphene nanoribbons (GNRs) with continuity at the edges. They overcome the as-yet unsolved difficulty to obtain scalable GNRs with atomically smooth edges, critical for electronics . To date there are very few reported Raman spectra of self-collapsed FCNTs, , and in these studies the objects were not identified as FCNTs but as GNRs.…”
mentioning
confidence: 99%
“…As one of the new carbon nanomaterials, carbon nanotubes have been the focus of intensive research because of their fascinating structures and properties [1]. Particularly, singlewalled carbon nanotubes (SWNTs) possess extraordinary electrical and optical properties, rendering them exciting candidates for nanoelectronics and optoelectronics [2,3]. To realize the proposed applications of SWNTs, it is necessary to synthesize SWNTs with controlled orientation, density, diameter, and even chirality.…”
Section: Introductionmentioning
confidence: 99%